2014
DOI: 10.1371/journal.pone.0114411
|View full text |Cite
|
Sign up to set email alerts
|

Unexpected Effects of Low Doses of a Neonicotinoid Insecticide on Behavioral Responses to Sex Pheromone in a Pest Insect

Abstract: In moths, which include many agricultural pest species, males are attracted by female-emitted sex pheromones. Although integrated pest management strategies are increasingly developed, most insect pest treatments rely on widespread use of neurotoxic chemicals, including neonicotinoid insecticides. Residual accumulation of low concentrations of these insecticides in the environment is known to be harmful to beneficial insects such as honey bees. This environmental stress probably acts as an “info-disruptor” by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
40
1
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 45 publications
(46 citation statements)
references
References 56 publications
(70 reference statements)
2
40
1
1
Order By: Relevance
“…In this study, we show that the dose-dependent modifications of pheromone-guided behaviour observed after clothianidin intoxication [17] might originate from the effect of insecticide treatments on the sensitivity of AL neurons to the sex pheromone. Indeed, single sensillum recordings and calcium imaging approaches show no significant effect of clothianidin at the used doses when compared with the corresponding solvent controls on the responses of individual ORNs and on the global input response in the AL.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…In this study, we show that the dose-dependent modifications of pheromone-guided behaviour observed after clothianidin intoxication [17] might originate from the effect of insecticide treatments on the sensitivity of AL neurons to the sex pheromone. Indeed, single sensillum recordings and calcium imaging approaches show no significant effect of clothianidin at the used doses when compared with the corresponding solvent controls on the responses of individual ORNs and on the global input response in the AL.…”
Section: Discussionmentioning
confidence: 72%
“…For stimulation in calcium imaging and intracellular recordings, an artificial behaviourally active pheromone blend containing (Z )-7-dodecen-1-yl acetate (Z7-12:OAc), (Z )-9-tetradecen-1-yl acetate (Z9 -14:OAc) and (Z )-11-hexadecen-1-yl acetate (Z11-16:OAc) at a ratio of 4 : 1 : 4 was used [19 -21] in order to compare physiological results with the previously acquired behavioural data [17]. For single-sensillum recordings, only the major pheromone component, Z7 -12:OAc, was used, because ORNs are tuned to individual pheromone compounds.…”
Section: (D) Odour Stimulationmentioning
confidence: 99%
“…However, there is still little information regarding the effects of sublethal dose/concentrations on insect behavior [21]. The sublethal doses of clothianidin on males of Agrotis ipsilon (Hufnagel) (Lepidoptera: Noctuidae) presented a "biphasic effect" with increased or decreased male pherome response depending on the insecticide dosage [22]. Sublethal doses of deltamethrin on Spodoptera littoralis (Boisduval) (Lepidoptera: Noctuidae) antennae cause an increased male response to the sex pheromone (hormesis effect), but it did not affect the male response to the host plant.…”
Section: Insect Behavior As a Measurement Of Insecticide Sublethal Efmentioning
confidence: 99%
“…Previous works mentioned that LC 50 (84 Nano-gram/L) of imidacloprid to larvae of Aedes aegypti. Uragayala et al evaluated the Larvicidal effect of neonicotinoid insecticides against susceptible and resistant mosquito's strains [82][83][84][85][86][87][88][89][90][91][92][93][94][95][96].…”
Section: Compoundsmentioning
confidence: 99%